Comparison of conventional and non-invasive diagnostic tools for detecting Plasmodium falciparum infection in southwestern Cameroon: a cross-sectional study - Tobias O. Apinjoh; Veronica N. Ntasin; Phil Collins C. Tataw; Vincent N. Ntui; Dieudonne L. Njimoh; Fidelis Cho-Ngwa; Eric A. Achidi (BMC, 2021)
Abstract Background Malaria remains a significant health challenge in sub-Saharan Africa, with early diagnosis critical to reducing its morbidity and mortality. Despite the increasing Plasmodium spp. diagnostic capabilities, access to testing is limited in some cases by the almost absolute requirement for blood from potentially infected subjects as the only sample source for all conventional methods. A rapid test on non-invasive specimen with comparable performance to microscopy for the screening or diagnosis of all participants is invaluable. This study sought to compare conventional and non-invasive diagnostic tools for detecting Plasmodium falciparum. Methods This was a cross-sectional study, carried out between March and August 2019 to evaluate and compare the diagnostic performance of a PfHRP2/pLDH-based malaria rapid diagnostic test (mRDT) on patients' blood, saliva and urine relative to conventional light microscopy and nested PCR at outpatient clinics in the Buea and Tiko health districts of Southwestern Cameroon. The significance of differences in proportions was explored using the Pearson's χ 2 test whereas differences in group means were assessed using analyses of variance. Results A total of 359 individuals of both sexes, aged 1-92 years, were enrolled into the study. Of the 301 individuals tested by light microscopy and mRDTs on blood, saliva and urine, 84 (27.9%), 81 (26.9%), 87 (28.9%) and 107 (35.5%) respectively were positive. However, only 34.3%, 90.5%, 91.4%, 83.9% and 65.4% febrile, light microscopy and mRDT positives on blood, saliva and urine respectively had P. falciparum infection as confirmed by PCR. The sensitivity and specificity of presumptive diagnosis, light microscopy and mRDT on blood, saliva and urine were 86.9% and 19.7%, 77.8% and 96.1%, 75.8% and 96.6%, 74.5% and 93.1%, and 70.7% and 81.8%, respectively. The agreement between mRDT on saliva (k = 0.696) and microscopy (k = 0.766) compared to PCR was good. Conclusion The study highlighted the low performance of presumptive diagnosis, reinforcing the need for parasitological tests prior to antimalarial therapy. The higher PfHRP2/pLDH mRDT parasite detection rates and sensitivity in saliva compared to urine suggests that the former is a practical adjunct to or alternative worth optimising for the routine diagnosis of malaria. Graphic Abstract Flow chart for diagnosis of P. falciparum infection by light microscopy, rapid diagnostic tests and nested PCR.